2010
DOI: 10.4161/pri.4.1.11074
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of amyloid formation in yeast

Abstract: In eukaryotic cells amyloid aggregates may incorporate various functionally unrelated proteins. In mammalian diseases this may cause amyloid toxicity, while in yeast this could contribute to prion phenotypes. Insolubility of amyloids in the presence of strong ionic detergents, such as SDS or sarcosyl, allows discrimination between amorphous and amyloid aggregates. Here, we used this property of amyloids to study the interdependence of their formation in yeast. We observed that SDS-resistant polymers of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 46 publications
6
17
0
Order By: Relevance
“…This indicates a possibility of sequestration of Sup35 by the aggresome, and agrees with the previous observation [43], confirmed by us (Figure 1E) that polyglutamines promote aggregation of a fraction of Sup35, even in a [ psi − ] strain. Notably, 103QP toxicity in the [ PSI + ] cells was ameliorated by introducing the Sup35 derivative (designated Sup35C) that lacks the N-terminal (prion) and middle domains and therefore, is functional but unable to be incorporated into the prion aggregates (Figure 1F).…”
Section: Resultssupporting
confidence: 92%
“…This indicates a possibility of sequestration of Sup35 by the aggresome, and agrees with the previous observation [43], confirmed by us (Figure 1E) that polyglutamines promote aggregation of a fraction of Sup35, even in a [ psi − ] strain. Notably, 103QP toxicity in the [ PSI + ] cells was ameliorated by introducing the Sup35 derivative (designated Sup35C) that lacks the N-terminal (prion) and middle domains and therefore, is functional but unable to be incorporated into the prion aggregates (Figure 1F).…”
Section: Resultssupporting
confidence: 92%
“…This was shown for htt with a polyQ stretch consisting of 103 Q (103Q) fused to the green fluorescent protein (GFP), which allows monitoring of 103Q-GFP aggregation microscopically, as distinct fluorescent foci. However, as we have shown previously, polyQ proteins could also form SDS-insoluble polymers in cells lacking these prions ([ psi − ] [ pin − ] cells) [9], [12]. This prompted us to study the dependence of 103Q-GFP polymerization on the [ PIN + ] prion.…”
Section: Resultsmentioning
confidence: 97%
“…Previously we have shown that aggregation of proteins with expanded polyQ, including mutant htt, in the cytoplasm of yeast cells caused polymerization of chromosomally-encoded Q/N-rich proteins [9]. Since there are a large number of proteins with long Q/N-rich stretches in both humans and yeast [10], [11], it is likely that at least some of them would efficiently polymerize in response to the accumulation of polyQ amyloids, which may cause depletion of their functional soluble form and, as a result, cell death, if these proteins are essential.…”
Section: Introductionmentioning
confidence: 99%
“…These model substrates share some similarities in that both are aggregationprone and they form large inclusions in yeast. Prions, such as [RNQ1] ϩ , are required for polyQ toxicity (16,17) and, likewise, polyQ aggregation influences prion formation (18). These results and many others (2,3,15).…”
mentioning
confidence: 85%